2007
DOI: 10.1152/jn.00646.2006
|View full text |Cite
|
Sign up to set email alerts
|

Giant Spontaneous Depolarizing Potentials in the Developing Thalamic Reticular Nucleus

Abstract: The thalamic reticular nucleus (nRt) provides a major source of inhibition in the thalamo-cortical circuit and is critically involved in the generation of spindle oscillations. Here we describe the properties of thalamic giant depolarizing potentials (tGDPs) that were observed in nRt during early development. tGDPs persisted in presence of ionotropic glutamate antagonists but were completely abolished by GABA(A)R antagonist SR 35591. tGDPs occurred primarily between p3 and p8 (in 30-50% of cells) and occasiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…It is also possible that delta sleep reductions are seen only in a subgroup of schizophrenia and their relationship to cognitive deficits is subtle and may have not reached significance. The evidence that thalamocortical gamma- amino butyric acid (GABA)ergic activity has a role in spindle generation (Pangratz-Fuehrer et al, 2007) may mean that the observed relationship between spindles and cognitive abilities in the present study supports the theory of GABA dysfunction in schizophrenia (Gonzalez-Burgos et al, 2010). This view is consistent with the view that alterations in selective attentional processes in schizophrenia may be mediated by thalamocortical circuits (Trenado et al, 2009, Crespo-Facorro et al, 2007).…”
Section: Discussionsupporting
confidence: 81%
“…It is also possible that delta sleep reductions are seen only in a subgroup of schizophrenia and their relationship to cognitive deficits is subtle and may have not reached significance. The evidence that thalamocortical gamma- amino butyric acid (GABA)ergic activity has a role in spindle generation (Pangratz-Fuehrer et al, 2007) may mean that the observed relationship between spindles and cognitive abilities in the present study supports the theory of GABA dysfunction in schizophrenia (Gonzalez-Burgos et al, 2010). This view is consistent with the view that alterations in selective attentional processes in schizophrenia may be mediated by thalamocortical circuits (Trenado et al, 2009, Crespo-Facorro et al, 2007).…”
Section: Discussionsupporting
confidence: 81%
“…Recent electrophysiological recordings in rats showed that during development GABA currents induce depolarization in TRN neurons, which is responsible for the bursting activity observed during spindles (46). These findings suggest that GABA currents/receptors in the TRN play a critical role in the development of spindles, and are consistent with the involvement of GABA deficits in the neurobiology of schizophrenia (47).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report found that GABAergic responses in non-dialyzed TRN cells are depolarizing from resting potential at ages younger than P8 (Pangratz-Fuehrer et al, 2007). Thus it would be expected that in young animals in vivo , depolarizing PSPs from GABAergic connections could summate with electrically-transmitted spikelets, leading to large, long lasting depolarizations.…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic physiological properties of the cells also change drastically, especially spike-bursting characteristics and passive membrane properties (Warren and Jones, 1997). During this early postnatal period TRN cells communicate via GABAergic transmission that is depolarizing due to a high intracellular chloride concentration until around postnatal day 9 (P9), after which GABA becomes clearly inhibitory (Pangratz-Fuehrer et al, 2007). No previous studies had tested whether TRN cells directly communicate via electrical synapses during early postnatal development.…”
Section: Introductionmentioning
confidence: 99%